Analysis of Air Side Needs at Mutiara SIS AL-JUFRI Airport Palu - Labaso, E.R.; Tahir, A.; Susilo, M. (Civil Engineering Department, Tadulako University, 2021)
The city of Palu is the capital of the province of central Sulawesi which has hajj waiting list 0f around 31,384 pilgrims with a qouta of 1986 pilgrims until 2034. Garuda indonesia has prepared four tipes of air craft that will serve these filghts including Boeing B777-300ER, B747-400, A330-300 and A330-200. In this study use the secondary data for the next 10 and 20 years forcasting uses the econometric method. The data needed includes climatology, passenger and air craft characteristic at Mutiara Al Jufri Airport. The standard refers to the ICAO. Based on the calculation result obtained that in the exixting condition, the length and width of the runway is 2,510 x 45 m and the width of taxiway is 23 m and the dimension of the apron are 373 x 311,2 m2. In 2027, the length of the runway will be 3786 m with a width of 45 m, and the width of taxiway 23 m. Apron dimension 541,5 x 195,5 m2. In 2037, the dimension of the runway and taxiway are still fixed, but the apron dimension changes to 714 x 195,5 m.